Developing a model to enhance the ability of elderly caregivers to provide an appropriated living environment in house in Phitsanulok province - Kongmaneekarn, Chomchai; Noosorn, Narongsak; Kanokthet, Thanach; Keeratisiroj, Orawan (Journal of Medical and Public Health Region 4, 2023)
This research is a mixed-method research design which aims to develop a model to enhance ability of elderly caregivers to provide an appropriated the environment in their houses by finding the relationship between variables affecting the ability of elderly caregivers in managing the environment in their houses. The research was divided into 3 phases. Phase 1 was qualitative research collecting data through in-depth interviews with 12 volunteer elderly caregivers to identify all relevant variables. Phase 2 was quantitative research using all variables identified in Phase 1 to develop a standardized questionnaire of 5 levels (Likert’s Scale) that was distributed to a sample of elderly caregivers in Phitsanulok province. The sample size was calculated using G*Power 3.1.9.2 software. The tool’s quality was checked by an expert and the sample was randomly selected in multiple steps by answer the questionnaires. Phase 3 was a focus group interview process to develop the model in ability of elderly caregivers in managing the environment in their houses. Data were analyzed using computer programs and statistical methods such as mean, percentage, standard deviation, and multiple regression analysis (MRA) were found female 86% and primary education 34% had only completed primary school. The variables that have a significant statistical positive impact on the ability of elderly caregivers are their attitude towards environmental management (β = 0.265, p< 0.001) and occupations for elderly caregivers (β = 0.165, p=0.016). However, being a member of various community clubs and organizations has a negative impact on the ability of elderly caregivers (β = - 0.140, p=0.042). The researcher used data from the study to create an AOM model (A: Attitude/Awareness/Action, O: occupation, M: Member of community clubs) to aid in the development of the abilities of elderly caregivers in the future. This can be used to further improve the care of the elderly and assist in planning and policy-making for elderly care.